2021
DOI: 10.1007/s42773-021-00099-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of biochar properties with changes in soil bacterial, fungal and fauna communities and nutrient cycling processes

Abstract: Soil microorganisms play crucial roles in soil nutrient cycling, carbon sequestration, fertility maintenance and crop health and production. To date, the responses of microorganisms, such as microbial activity, diversity, community structure and nutrient cycling processes, to biochar addition have been widely reported. However, the relationships between soil microbial groups (bacteria, fungi and microscopic fauna) and biochar physicochemical properties have not been summarized. In this review, we conclude that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(65 citation statements)
references
References 129 publications
3
61
0
1
Order By: Relevance
“…CEC represents the bulk of cations associated to the biochar surface. The CEC of soil tended to increase effectively after the addition of biochar due to the presence of the functional group and negative charge on the surface of biochar [41]. The results were similar to the findings of Peng et al [38] who reported that RS-derived biochar significantly raised the pH value by 0.1 to 0.46 units in soil and increased the CEC of soil by 17%.…”
Section: Improvement Of Soil Supplemented With Rs-bc and Wb-bcsupporting
confidence: 88%
“…CEC represents the bulk of cations associated to the biochar surface. The CEC of soil tended to increase effectively after the addition of biochar due to the presence of the functional group and negative charge on the surface of biochar [41]. The results were similar to the findings of Peng et al [38] who reported that RS-derived biochar significantly raised the pH value by 0.1 to 0.46 units in soil and increased the CEC of soil by 17%.…”
Section: Improvement Of Soil Supplemented With Rs-bc and Wb-bcsupporting
confidence: 88%
“…It indicated that the appropriate concentration of biochar addition could enhance the accumulation of N and the fixation of C, and possibly accelerate the progress of plant life activities, resulting in the accumulation of more nutrients [ 50 ]. The reasons for this may be the addition of biochar directly affects the microbial activity in the rhizosphere of the moss crusts to promote the conversion of nitrogen and phosphorus, thereby increasing the nitrogen and phosphorus content of the moss crust, and finally the C: N: P stoichiometric ratio of the moss crust is changed, and the C content also increases [ 51 , 52 ]. Furthermore, several studies have shown that biochar not only increased the K concentration in soil but also increased the plant nutrient use efficiency of K, which is important for plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis conducted by Li et al (2020) has concluded that biochar properties govern soil microbial biomass, whereas soil properties determine soil microbial diversity. A clear effect on the microbial growth, diversity, and community compositions in soil was observed after the addition of biochar, which provides growth promotion due to the change in soil properties (Dai et al, 2021). This was governed by the porosity, labile C, alkaline pH, and CEC of biochar, and it varies with biochar types, production temperature, and feedstock type (Dai et al, 2021).…”
Section: Impact Of Biochar On Soil Microbial Diversity and Abundancementioning
confidence: 99%